3D-CT-derived lung volumes and mortality risk in patients with fibrotic hypersensitivity pneumonitis - Shusuke Yazawa; Yuzo Suzuki; Yuko Tanaka; Koshi Yokomura; Masato Kono; Dai Hashimoto; Atsuki Fukada; Yusuke Inoue; Hideki Yasui; Hironao Hozumi; Masato Karayama; Kazuki Furuhashi; et al. (Allergology International)
Background: Hypersensitivity pneumonitis (HP) is a complex and heterogenous interstitial lung disease (ILD) that occurs in susceptible individuals due to certain inhaled antigens. Fibrotic-HP is a major underlying disease of progressive pulmonary fibrosis. Therefore, in addition to the radiological features of HP, quantitatively measuring fibrosis is important to evaluate disease severity and progression. The present study aimed to compare three-dimensional computed tomography (3D-CT)-derived lung volumes (LVs) of patients with HP and determine its association with mortality risk. Methods: In this retrospective and multicenter cohort study, 126 patients diagnosed with HP (fibrotic, n = 72 and non-fibrotic, n = 54) with a confidence level higher than moderate were enrolled. Each lobe LV was measured using 3D-CT at the time of diagnosis and standardized using predicted forced vital capacity. The 3D-CT LV was compared with those of 42 controls and 140 patients with idiopathic pulmonary fibrosis (IPF). Results: Compared to patients with fibrotic-HP, the standardized total LV was significantly higher in controls and patients with non-fibrotic-HP and was similar in patients with IPF. Longitudinal analyses demonstrated that approximately half of the patients with fibrotic-HP had an annual decrease in total LV. Decreased total and lower-lobe LVs were associated with shorter survival, and were independently associated with mortality together with ongoing exposure to inciting antigens. A composite model consisting of ongoing exposure to inciting antigens and total or lower-lobe LV successfully classified mortality risk into three groups. Conclusions: Quantitatively measuring standardized LV can help determine disease severity, progression, and mortality risk in patients with fibrotic-HP.